Students' Mathematical Literacy Ability in Calculus Courses in Online Learning at the University of Semarang - Yulinda Kusumaningrum; Charis Maulana; Agus Edy Laksono (Universitas Islam Sultan Agung, 2022)
Learning calculus in an online class is very challenging for students. This type of research is qualitative with the aim of explaining students' mathematical literacy skills in calculus courses. The sample for this study were three students out of 38 students who took electrical engineering courses. The students consisted of different levels of initial mathematical ability, namely high (score 80), medium (scores between 50 to 80) and low (less than 50) in calculus courses. Test and interview methods were used to collect data. The results showed that students with high mathematical abilities (S1) were at level 4 of their literacy skills and the percentage score reached 78.3%. Students with medium mathematical abilities (S2) are at level 3 of mathematical literacy skills with a score percentage reaching 62.5% and for students with low mathematical abilities (S3) are at level 2 literacy skills and the percentage score reaches 46.6%.